The Effect of Guided Inquiry Learning with Mind Map to Science Process Skills and Learning Outcomes of Natural Sciences - Hilman (Universitas Negeri Malang, 2015)
Pengaruh Pembelajaran Inkuiri Terbimbing dengan Mind Map terhadap Keterampilan Proses Sains dan Hasil Belajar IPA   Abstract: Science learning in junior high school aims to enable students conducts scientific inquiry, improves knowledge, concepts, and science skills. Organization materials for students supports learning process so that needs to be explored techniques that allows students to enable it. This study aimed to determine the effect of guided inquiry learning with mind map on science process skills and cognitive learning outcomes. This experimental quasi studey used pretest-posttest control group design and consisted eighth grade students of SMP Negeri 1 Papalang Mamuju of West Sulawesi. The results showed there where significant positive effect of guided inquiry learning with mind map on process science skills and cognitive learning outcomes. Key Words: guided inquiry, mind map, science process skills, cognitive learning outcomes   Abstrak: Pembelajaran Ilmu Pengetahuan Alam (IPA) di SMP bertujuan agar siswa dapat melakukan inkuiri ilmiah, meningkatkan pengetahuan, konsep, dan keterampilan IPA. Dalam pembelajaran, organisasi materi berperan penting dalam memudahkan anak belajar sehingga perlu ditelaah teknik yang memudahkan siswa membuat organisasi materi. Penelitian ini bertujuan mengetahui pengaruh pembelajaran inkuiri terbimbing dengan mind map terhadap keterampilan proses sains dan hasil belajar kognitif. Penelitian kuasi eksperimen ini menggunakan rancangan pre test-post test control group design dengan subjek penelitian siswa kelas VIII SMP Negeri 1 Papalang. Hasil penelitian menunjukkan ada pengaruh positif yang signifikan pembelajaran inkuiri terbimbing dengan mind map terhadap kemampuan keterampilan proses sains dan hasil belajar kognitif siswa. Kata kunci:  inkuiri terbimbing, mind map, keterampilan proses sains,  hasil belajar kognitif